A genome‐wide association study suggests that MAPK14 is associated with diabetic foot ulcers3. (27th November 2017) - Meng, W.; Veluchamy, A.; Hébert, H.L.; Campbell, A.; Colhoun, H.M.; Palmer, C.N.A.
Summary: Background: Diabetic foot ulcers (DFUs) are a devastating complication of diabetes. Objectives: To identify genetic contributors to the development of DFUs in the presence of peripheral neuropathy in a Scottish cohort with diabetes using a genome‐wide association study. Methods: A genome‐wide association approach was applied. A case was defined as a person with diabetes (type 1 or type 2) who had ever had a foot ulcer (current or previous) in at least one foot, as well as a positive monofilament test result (i.e. evidence of peripheral neuropathy) recorded in their longitudinal e‐health records. A control was defined as an individual with diabetes (type 1 or type 2) who has never been recorded as having a foot ulcer in either foot but who had a positive monofilament test result recorded in either foot in their longitudinal e‐health records. Results: There were 699 DFU cases and 2695 controls in the Genetics of Diabetes Audit and Research in Tayside Scotland (GoDARTS) dataset. The single‐nucleotide polymorphism rs80028505 (Chr6p21·31) in MAPK14 reached genome‐wide significance with a lowest P ‐value of 2·45 × 10 −8 . The narrow‐sense heritability of this phenotype is 0·06. Conclusions: We suggest that MAPK14 is associated with DFUs. Abstract : What's already known about this topic? Around 25% of people with diabetes will develop foot ulceration in their lifetime. Diabetic foot ulcers (DFUs) account for 85% of all lower‐limb amputations in the U.K. There are multiple risk factors for DFUs, the strongest initiating factor being peripheral sensory neuropathy. The genetics of DFUs are poorly understood. What does this study add? This genome‐wide association study suggests that a skin‐related gene, MAPK14, is associated with DFUs in individuals with evidence of neuropathy. The narrow‐sense heritability of this disorder, in individuals with evidence of neuropathy, is 0·06. What is the translational message? Genetic variants in MAPK14 are strongly linked with DFUs. Further study is needed to confirm the gene's role, followed by clinical trials that should bring significant benefits to patients with DFUs. Linked Comment:Lainer. Br J Dermatol 2017;177 :1482–1483 . Plain language summary available online Respond to this article